Under the affluence : shaming the poor, praising the rich and sacrificing the future of America - Wise, Tim. 1968- (City lights open media, 2015)
""One of the most brilliant, articulate, and courageous critics of white privilege in the nation."--Michael Eric DysonTim Wise is one of America's most prolific public intellectuals. His critically acclaimed books, high-profile media interviews, and year-round speaking schedule have established him as a leading voice for racial equity. In Under the Affluence, Wise builds on his fierce critique of racial privilege to discuss a related issue: class disparity and a culture of cruelty that demonizes those in need.As Wise demonstrates, there was a time when the hardship of fellow Americans stirred feelings of sympathy, civic responsibility, and direct support for policies meant to alleviate poverty. But today, mainstream discourse increasingly blames low-income folks for their own situation, and the notion of an intractable "culture of poverty" has pushed our country in an especially ugly direction. Wise shows how the wealthy elite have commandeered discussions about class, moving the nation toward scorn and disengagement from the marginalized.With clarity and precision, Wise not only documents growing contempt for the nation's have-nots, but also explores the underlying forces that perpetuate it. In doing so, he demonstrates how classism, racism, and sexism are inextricably linked, and how popular culture contributes to a deepening indifference to those who are struggling. Finally, Wise shows that far from a culture of poverty, it is the culture of affluence and power that deserves the blame for America's simmering economic and social crises.Tim Wise is the author of many books, including Dear White America and Colorblind"--